Impact of Fiscal Policy Adjustment Based on Islamic Economics on Infrastructure Development in Muslim Countries - Abdallah Al-Shreifeen, Iyad; Nazmul Husain, S. M.; Apriani, Triana (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
This article examines the impact of fiscal policy adjustments based on Islamic economics on infrastructure development in Muslim-majority countries. Islamic economics emphasizes justice, equity, and the ethical management of resources, offering alternative solutions to conventional financing for infrastructure projects. The study focuses on the role of Islamic financial instruments, particularly sukuk (Islamic bonds) and zakat (almsgiving), in funding infrastructure development in a Sharia-compliant manner. Through case studies from Malaysia, Saudi Arabia, and Indonesia, the article shows how sukuk has been successfully utilized to finance large infrastructure projects, including transportation, energy, and urban development, while avoiding interest-based debt. Additionally, zakat is explored as a potential source for funding social infrastructure projects, though challenges in fund management and coordination are noted. The findings suggest that Islamic fiscal policies can offer effective solutions for promoting sustainable, equitable, and inclusive infrastructure development. By aligning fiscal policy with Islamic principles, Muslim-majority countries can address infrastructure gaps and foster long-term economic and social welfare.